FAITH AND FORGIVENESS: LUKE 7,36-50 - Kilgallen, John J. (Revue biblique, 2005)
Luke acknowledged what Mark had suggested in the story of the paralytic (Mk 2, 1-12: Lk 5, 17,26): 1. - that the forgiveness of the paralytic's sins was the effect of his ("their") faith; 2. - that Jesus forgave the man his sins. Luke's use of the perfect of aphiémi means to highlight the relationship of previous faith to previous forgiveness. All this is extremely useful in explaining the forgiveness of sins in Acts as the result of faith. Luke 7 also insists, again through the use of apheôntai, that the woman had been forgiven before coming to Jesus at Simon's dinner, a forgiveness resulting from her earlier response to Jesu's call to repentance. What Luke has arranged in 7, 36-50, however, is a further consideration, which is also an enlightenment to the woman who thought of Jesus as the bearer of good news to her: he, she learns, is the one who forgave her. Luc exprime ce que Marc avait suggéré dans l'histoire du paralytique (Mc 2, 1-12 I Lc 5, 17-26), à savoir : 1. – que le pardon des péchés du paralytique était le résultat de sa (« leur ») foi ; 2. – que Jésus avait pardonné à l'homme ses péchés. L'usage du parfait de aphiémi par Luc veut souligner le lien entre la foi et le pardon qui précèdent tous deux. Cela est fort utile pour expliquer le pardon des péchés comme résultant de la foi, en Actes. Luc 7 insiste aussi, de nouveau par l'usage de apheôntai, sur le fait que la femme a été pardonnée avant l'arrivée de Jésus au dîner de Simon, un pardon résultant de sa réponse préalable à l'appel de Jésus au repentir. Toutefois, ce que Luc a combiné, en 7, 36-50, est un enrichissement, lequel est aussi une illumination pour la femme qui avait pensé que Jésus était porteur de bonnes nouvelles : elle apprend qu'il est celui qui lui a pardonné.